Identification of novel chemical scaffolds Inhibiting trypanothione synthetase from pathogenic trypanosomatids - Benítez, Diego (2016)
Fil: Fil: Benítez, Diego. Institut Pasteur de Montevideo. Laboratorio de Biologia Redox de Tripanosomátidos; Uruguay.